Peran Pecalang dalam Memelihara Pluralitas Beragama di Pulau Lombok - Ilhami, Hablun; Truna, Doddy S.; Halim, Ilim Abdul (Universitas Negeri Medan, 2024)
Religious plurality has the highest positive-negative potential among several aspects of plurality that exist. This is inseparable from the multifaces of religion. This paper aims to explore the role of Pecalang in maintaining religious plurality on Lombok Island by focusing on three problem formulations, namely: how Pecalang are in religious plurality on Lombok Island, how Pecalang as a minority group and the face of plurality on Lombok Island, and how Pecalang maintain religious plurality on Lombok Island. This paper is based on qualitative research with data sources from the Sasak and Balinese communities on Lombok Island. The data obtained through the interview method were then interpreted using Talcott Parsons' structural functional theory. The results of the analysis show that Pecalang as a task force that is traditionally a Balinese Hindu culture in the midst of the Sasak Muslim community is a fact of religious plurality on Lombok Island. Pecalang as a Balinese Hindu minority group living in the midst of the Sasak Muslim majority tries to maintain or safeguard the peace, security and stability of religious plurality on Lombok Island. This can be seen from how Pecalang adapts, sets shared social goals, integrates or cooperates with other community groups, and maintains stability by conducting